Edukasi Gizi mengenai Pencegahan Malnutrisi pada Ibu Balita Gizi Kurang - Arnati Wulansari; Dini Junita (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
The problem of malnutrition in children underfive is still major nutritional problem that needs attention. Nutritional problems are directly caused by inadequate intake and high infectious disease. This is related to environmental sanitation and inadequate health services, impaired access to food, inadequate maternal care and the lack of knowledge of mothers about how to give good food to children of weaning age. For this reason, counseling activities are needed as an effort to increase the knowledge of mothers of children under five related to malnutrition. The method of implementing community service activities is in the form of counseling and evaluation of pre and post tests. Monitoring is carried out by identifying indicators of success in aspects of attendance, reflection, and feedback from participants. After education, there was an increase in knowledge from the post test evaluation results with a good knowledge category of 100%. It was concluded that this activity could increase the knowledge of mothers under five regarding the prevention and control of malnutrition. The program can be continuous with the cooperation of health workers at the Pamenang Health Center